Smart micro-credentials in higher education: enhancing student engagement in probability learning - Awang Chek, Mohd Zaki; Ismail, Isma Liana; Abdul Razak, Norfadzilah (2025)
In an era where digital learning continues to transform the educational landscape, micro-credentials have emerged as a viable alternative to traditional degree programs. This study investigates the effectiveness of micro-credentials in Probability education within the UiTM Learning Management System (LMS), particularly the Ufuture platform (https://ufuture.uitm.edu.my/courses/overview/UMC379). The research aims to evaluate student satisfaction, knowledge acquisition, and engagement in the micro-credential course Counting and Probability, offered at UiTM. By leveraging learning analytics, the study examines student interactions, assessment results, and engagement patterns to provide actionable insights into the efficacy of micro-credentials in statistical education. Using a survey-based quantitative approach, data was gathered from 74 undergraduate students enrolled in the micro-credential course, assessing seven key dimensions: knowledge gain, content relevance, assessment effectiveness, confidence improvement, instructional delivery, instructor approachability, and overall enjoyment. Statistical techniques, including descriptive analysis and correlation analysis were applied to interpret student responses. The findings reveal a high level of satisfaction, with an average rating above 4.6 across all dimensions. The strongest correlation was identified between engaging instructional methods and overall enjoyment, underscoring the importance of interactive pedagogical strategies.Micro-credentials developed within Ufuture UiTM are structured to facilitate self-paced learning while maintaining rigorous academic standards. The Counting and Probability module covers fundamental probability concepts, including Set Theory, Probability Rules, and Bayes’ Theorem, incorporating adaptive learning technologies, gamification, and interactive problem-solving exercises. Learning analytics data from Ufuture revealed that students engaging with interactive content demonstrated higher assessment scores and improved retention rates compared to those relying solely on textual materials. Furthermore, instructor accessibility and assessment clarity emerged as critical factors influencing learner confidence and engagement. While the study confirms the effectiveness of micro-credentials in Probability education, minor disparities in satisfaction levels suggest potential areas for improvement. Specifically, personalized feedback mechanisms, real-world application scenarios, and adaptive learning pathways should be enhanced to address diverse learner needs. The integration of AI-driven learning recommendations and peer interaction forums is recommended to further elevate engagement and learning outcomes. This research contributes to the broader discourse on micro-credentials in higher education, offering empirical evidence on their impact in Probability education. Future initiatives should focus on optimizing content delivery through data-driven instructional design and expanding micro-credential offerings in other mathematical domains. By leveraging learning analytics, UiTM’s Ufuture platform can continue to refine its digital learning ecosystem, ensuring a student-centric, data-informed approach to higher education.